Dermatomal rash after Shingrix vaccination: cause or coincidence?. Issue 5 (15th September 2022) - Mittal, Nitish; Dhir, Nikita; Mittal, Neha
Abstract: Dermatological reactions have been reported following Shingrix vaccine administration in previous published cases, but dermatomal rash after Shingrix vaccination has not been reported in the United States. This case describes a 73-year-old immunocompetent woman with a dermatomal rash after Shingrix recombinant vaccine administration. This case highlights the rare possibility of an acute reaction after Shingrix vaccine administration, which should be recognized. Nonetheless, the vaccine has been shown to be very effective at preventing varicella zoster virus reactivation and postherpetic neuralgia, so the benefit of receiving the vaccination significantly outweighs the risk.